TEKNIK RELAKSASI GENGGAM JARI TERHADAP INTENSITAS NYERI PADA PASIEN POST APPENDIKTOMI - Sulung, Neila; Rani, Sarah Dian (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
Pain is a condition more than a single sensation caused by a certain stimulus. One of the non-pharmacological erections in handling pain is a hand-held relaxation technique. Finger hand-held real-time techniques can reduce physical and emotional strain that will relax the body. This study aims to examine the effect of finger hand relaxation technique on the intensity of pain in post appendectomy patients. This research uses Quasy Experiment design with One Group Pre-test Post- Stestdesign. The total population of this study were all patients of post appendectomy in Achmad Mochtar Hospital. Sampling technique using purposive sampling technique. This study was conducted on February 17 until 1 May 2017 in the hospital surgery room Achmad Mochtar Bukittinggi. Data were analyzed by using Paired T-Test with significant value α = 0,005. The results showed that the average before hand-held finger relaxation technique was 4.80 and the mean result after hand-held relaxation technique was 3.87. Bivariate results obtained p value 0,000. So it shows there are differences in pain intensity before and after hand-held relaxation techniques in patients post appendectomy. From the results of the above research can be concluded that the implementation of handheld relaxation techniques affect the reduction of post incision appendectomy incision.